Effect of Polyaniline on the Ionic Conductivity of PVA/NaCl Composite Electrolyte Membranes - Firman Ridwan; Muhammad Akbar Husin (ASEAN Journal of Chemical Engineering, 2025)
This study investigates the effect of polyaniline (PANI) on the ionic conductivity and performance of polyvinyl alcohol (PVA)/sodium chloride (NaCl) composite electrolyte membranes for application in aluminum-air batteries. PVA/NaCl/potato starch (PS) membranes with varying PANI concentrations (0, 1, 1.5, and 2 g) were prepared and characterized. Tensile strength tests revealed that increasing PANI content led to increased brittleness and decreased elastic properties of the membranes. Electrochemical impedance spectroscopy showed that adding 2 g of PANI resulted in the highest ionic conductivity of 1.69 mS/cm. Galvanostatic discharge tests demonstrated that the membrane with 1.5 g of PANI exhibited the longest operational time of 677 s at 1 mA and the highest initial voltage of 1.42 V. The battery with 1.5 g of PANI in the electrolyte membrane also achieved the highest electrical capacity of 0.188 mAh. However, excessive PANI content (2 g) led to a decrease in battery performance. The results suggest that the optimal PANI concentration for enhancing the performance of PVA/NaCl/PS electrolyte membranes in aluminum-air batteries is 1.5 g. This study highlights the potential of PANI as an additive for improving the ionic conductivity and performance of composite electrolyte membranes in Al-air batteries.